2017
DOI: 10.1007/s00795-017-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of Klotho and DNA methyltransferase 3a in oral squamous cell carcinomas

Abstract: Carcinoma follows a course of multiple changes that are affected by several important factors, with epigenetic silencing of the promoter gene being one of them. A series of studies have suggested that epigenetic changes in the anti-aging gene Klotho may be one of the emerging areas of concern in the study of carcinogenesis. We hypothesized that epigenetic silencing of Klotho due to hypermethylation of DNMT3a may be one of the causes of carcinoma in the oral and maxillofacial region. In this study, we analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…In cases of highly malignant, poorly differentiated, and anaplastic thyroid cancers (except one sample) the immunoreaction with A-9 anti-a-Klotho antibody was negative or very weak. This is compatible with many data showing the down-regulation of the a-Klotho expression in such human neoplasms as pancreatic [2,13], breast [3], oral squamous cell [8], cervical [14], and gastric cancer [15]. Recently, it was also found that a protein similar to a-Klotho, namely b-Klotho, is decreased in the blood serum of patients with thyroid cancers vs. patients with benign nodular goitre [16].…”
Section: Immunostaining With Epr6856 Antibodysupporting
confidence: 90%
See 1 more Smart Citation
“…In cases of highly malignant, poorly differentiated, and anaplastic thyroid cancers (except one sample) the immunoreaction with A-9 anti-a-Klotho antibody was negative or very weak. This is compatible with many data showing the down-regulation of the a-Klotho expression in such human neoplasms as pancreatic [2,13], breast [3], oral squamous cell [8], cervical [14], and gastric cancer [15]. Recently, it was also found that a protein similar to a-Klotho, namely b-Klotho, is decreased in the blood serum of patients with thyroid cancers vs. patients with benign nodular goitre [16].…”
Section: Immunostaining With Epr6856 Antibodysupporting
confidence: 90%
“…In the above-mentioned paper it was shown that the overexpression of Klotho induces the inhibition of growth and increases apoptosis in follicular thyroid cancer cell lines in vitro. Moreover, in contrast to the numerous studies on a-Klotho expression done by means of molecular biology techniques, immunohistochemical studies were very scarce, as well in cancers as in normal tissues [8,9]. The present paper reports the immunohistochemical investigation of a-Klotho in benign thyroid lesions and thyroid cancers.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, overexpression of DNMT1 was an independent marker of poor clinical outcome and relapse-free survival of OSCC patients (Supic et al 2017). Another study also confirmed upregulation of DNMT3a in OSCC, in connection with low expression of Klotho, the anti-aging gene (Adhikari et al 2017). Chen et al (2016b) revealed that in invasive subclone HNSCC cell lines, DNMT3b was upregulated, while E-cadherin was downregulated, suggesting that DNMT3B may be involved in induction of epithelial-mesenchymal transition (EMT).…”
Section: Dnmtmentioning
confidence: 87%
“…Moreover, ChIP results showed that DNMT3a and Klotho promoters were highly enriched in HG environment, and the enrichment was reduced after EGCG intervention. The effect of DNMT3a on Klotho promoter methylation has been reported in several studies [37,46,47]; however, the binding of DNMT3a to Klotho gene promoters was not reported. In this study, for the first time, we showed that EGCG decreased the enrichment of DNMT3a in the Klotho gene promoter under HG conditions.…”
mentioning
confidence: 95%